Reception history, tradition and biblical interpretation: Gadamer and Jauss in current practice - Evans, Robert (Scriptural traces: critical perspectives on the reception and influence of the Bible, 2014)
Introduction : impulses and parameters of this study -- Reception history and historical-critical exegesis -- The case study and historical-critical tools : genre and the Erwartungshorizont -- The case study and historical-critical tools : lexis and the Erwartungshorizont -- The case study and historical-critical tools : socio-historical setting and the Erwartungshorizont -- Reception history and the progressive process -- The case study : contours of a tradition in the church -- The case study : contours of a tradition in literature -- Reception history and theological hermeneutics -- The case study and theological hermemeutics -- Conclusion